Nilai-Nilai Religius dalam Novel “Bulan Terbelah di Langit Amerika” Karya Hanum Salsabiela Rais dan Rangga Almahendra - Nurul Fatimah (Jurnal Tarbiyatuna : Kajian Pendidikan Islam, 2017)
One of literary work in the novel that are phenomenal at this time is novel titled “Split Moon in the Sky America” by Hanum Salsabiela Rais and Rangga Almahendra. Genre of the novel is very different from other novels. Novel that reveals the mystery of 9/11 or often called black Tuesday able to arouse the reader’s heart. Without Islamic. Will world beautiful? All answered in this novel. It also presents a novel religious values associated with the god and among the others. So the experts looked at the novel’s literary quality because not only giving entertainment but also inculcating religious value are easily understood and implemented by the reader in everyday life